Incidence of esophageal lesions in patients undergoing ablation for atrial fibrillation with multipolar pulmonary vein ablation catheter (PVAC-GOLD®) - David da Silva, Renato; Arantes Filho, Ruiter Carlos; Araújo, Liélia Malaquias da Cunha; Araújo, Liélia Malaquias da Cunha; Margalho, Carla Septimio; Macedo da Rocha, Jairo; Seixas, Tamer Najar; Maria, Henrique César; Péres, Ayrton Klier (JOURNAL OF CARDIAC ARRHYTHMIAS, 2018)
Background: Esophageal lesions are described as a complication after ablation for atrial fibrillation. The studies evaluating the development of esophageal lesions in ablation due to atrial fibrillation had unipolar mode radiofrequency energy source using an irrigated catheter. A multipolar pulmonary vein ablation catheter (PVAC-GOLD®) is currently available, which uses phase-in cycles of energy (Duty-Cycled Phased RF). This study aims to evaluate the occurrence of esophageal lesions in patients undergoing ablations due to atrial fibrillation using the PVAC-GOLD® catheter. Method: Between August 2014 and August 2017, patients undergoing ablation due to symptomatic atrial fibrillation with the use of the PVAC-GOLD® catheter were included in the study. Upper digestive endoscopy was performed in the postoperative period to determine the presence of thermal esophageal lesions associated to the procedure. Results: A total of 117 patients, with mean age of 54.8 years, predominantly males, were included in the study. Of these patients, only 2 presented thermal esophageal lesions diagnosed by endoscopy. Conclusion: Esophageal lesion seems to be an unusual finding in patients undergoing electrical isolation of the pulmonary veins sing the multipolar pulmonary vein ablation catheter (PVAC-GOLD®).